Hubungan Asupan Serat, Asupan Natrium Dan Aktivitas Fisik Dengan Tekanan Darah Di Unit Rawat Jalan UPTD Puskesmas Pajang Surakarta - Putri, Mery Andika, Ibu Endang Nur W, SST, M.Si Med, Ibu Ririn Yuliati S. ST., M.Si (2016)
Introduction: Low fiber intake, excess sodium intake and physical inactivity will affect the increased blood volume, so the eventally it will ucrease the blood pressure. Objective:To determine the relationship of fiber intake, sodium intake and physical activity on blood pressure mout patient of UPTD Puskesmas Pajang Surakarta. Research method:This is an Observational research with cross sectional approach. A total of 44 subjects, were selected user consecutive sampling method. Fiber and sodium intake were obtained using semiquantitative FFQ, while physical activity was obtained using physical activity recall, method blood pressure was measured sphygmomanometer. All data were analyted using Pearson product moment or Spearman rank test. Results: A total of 81.7% of the subjects had low fiber intake and 43.2% of the subjects had hish sodium intake. 75.1% of the subjects had mild physical activity and 41% of the subject had hypertension stage 1 based on systolic blood pressure and 45.5% of the subjects had a of hypertensive stage 1. Based diastolic blood preassure there is an association of fiber intake with systolic blood pressure (p = 0.011) and diastolic (p = 0.002). There is also an association of sodium intake with systolic blood pressure (p = 0.046) and diastolic (p = 0.034). However, no association werefound on physical activity with either systolic (p = 0.013) or diastolic blood preassure (p = 0.024). Conclusion : This study concluded that there is an association of fiber intake, sodium intake with blood pressure in outpatient UPTD Puskesmas Pajang Surakarta. However no association was found on physical activity with blood preassure in outpatien of UPTD Puskesmas Pajang Surakarta.